Subarachnoid haemorrhage mimicking unstable angina: a case report - Chand, Subhash; Chander, Subhash; Gargi, Gaveshna; Sharma, Tarun; Sharma, Rittin (International Journal of Research in Medical Sciences, 2020)
Subarachnoid haemorrhage (SAH) is medical emergency caused by bleeding into the subarachnoid space. It is caused by rupture of an aneurysm or arteriovenous malformations (AVM). Symptoms of SAH are severe headache, nausea, vomiting, impaired consciousness and seizures. Neck stiffness and neck pain are relatively uncommon. Risk factors are high blood pressure, smoking, family history, alcoholism and even cocaine use. Diagnosis is mainly made by CT scan of head which should be done within six hours of the onset of symptoms and occasionally lumber puncture can also be done. An electrocardiogram (ECG) of all patients with subarachnoid should be done because patient with SAH can have myocardial ischemia due to increased level of circulating catecholamines or due to autonomic stimulation of the brain. ECG changes associated with SAH primarily reflect repolarisation abnormalities involving ST segment, T wave, U wave and QTc interval. Myocardial ischemia or infarction is often suspected in patients with SAH. Even troponin levels may be raised in these patients. However, suspicion of SAH is a contraindication for thrombolytic and anticoagulant therapy. This is a case of SAH which was initially treated for acute coronary syndrome (ACS) on the basis of symptoms and gradually changing ECG findings but on CT Head, patient was having SAH.